2011
DOI: 10.1007/s10393-011-0727-5
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Infections, Anemia and Malnutrition Among Rural Settled and Mobile Pastoralist Mothers and Their Children in Chad

Abstract: Malnutrition, resulting from various etiologies, is common in rural Chadian women and children. This cross-sectional study assessed the spectrum of parasitic infection and level of anemia and their effect on nutritional status in settled and mobile pastoral mothers and children near Lake Chad. Intestinal parasites were evaluated using direct fecal smears and the Kato–Katz technique. Malaria status was determined using Paracheck-Pf® rapid diagnostic test, and anemia was assessed with the Hemocue photometer. Nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
1
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 21 publications
(25 reference statements)
1
55
1
13
Order By: Relevance
“…Nevertheless, both methods used have the advantage of being simple, rapid, and inexpensive, and are suited for low-income countries (OMS, 1983;Tchuem Tchuenté , 2012). The prevalence rate of 57.1% corroborates those already found: 57.7% in N"Djamena by Kostoingue et al (2002), 51% also in N"Djamena by Hamit et al (2008), 56 % in other tropical regions as in Gondar ( Ethiopia) by Worku et al (2009), 54.7% in the Delta state (Nigeria) by Egwunyenga et al (2005), 60% in the region of Lake Chad by Bechir et al (2011), and 60% in The rate of infection was higher in boys than in girls (Table 3). This observation has been reported by several authors such as: Kassi et al (1989) in Aboisso, Menan et al (1997) in Abidjan, Adou-Brin (2001) in Toumodi and Stephane et al (2004) in Agboville (Ivory Coast), Tchuem Tchuenté et al (2012) in the Center, East and West regions of Cameroon.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Nevertheless, both methods used have the advantage of being simple, rapid, and inexpensive, and are suited for low-income countries (OMS, 1983;Tchuem Tchuenté , 2012). The prevalence rate of 57.1% corroborates those already found: 57.7% in N"Djamena by Kostoingue et al (2002), 51% also in N"Djamena by Hamit et al (2008), 56 % in other tropical regions as in Gondar ( Ethiopia) by Worku et al (2009), 54.7% in the Delta state (Nigeria) by Egwunyenga et al (2005), 60% in the region of Lake Chad by Bechir et al (2011), and 60% in The rate of infection was higher in boys than in girls (Table 3). This observation has been reported by several authors such as: Kassi et al (1989) in Aboisso, Menan et al (1997) in Abidjan, Adou-Brin (2001) in Toumodi and Stephane et al (2004) in Agboville (Ivory Coast), Tchuem Tchuenté et al (2012) in the Center, East and West regions of Cameroon.…”
Section: Discussionsupporting
confidence: 79%
“…A similar finding had been published for the first two species by Brooker et al (2000) in Cameroon, Saathoff et al (2005) in South Africa, Goodman et al (2007) in Zanzibar, Hamit et al (2008) in Chad, and Zephania et al (2010) in Cameroon. Recently, Bechir et al (2011) demonstrated the prevalence of hookworm in Chad. The higher rate of ascaridiasis (33.7%) in the present study confirms that this parasitosis is one of the most common in the world among geohelminthiases (Tchuem Tchuente et al, 2001Montresor et al, 2002;Miguel & Kremer, 2002, Ajeagah et al, 2013.…”
Section: Journal Of Biology and Life Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…In present study we found that Children with Tuberculosis presented with fever (22, 95.7%); cough (15, 65.2%); H/o Koch's contacts (19,82.6%); pain abdomen (5, 21%); pallor (22, 95.7%); lymphadenopathy (22, 95.7%), and chest-crepts (10, 43.5%). Marais BJ et al found that children with Tuberculosis presented with persistent non remitting cough of > 2 weeks' duration, documented failure to thrive (in the preceding 3 months), and fatigue provided reasonable diagnostic accuracy in HIV uninfected children (sensitivity: 62.6%; specificity: 89.8%; positive predictive value: 83.6%); the performance was better in the low-risk group (> or = 3 years; sensitivity: 82.3%; specificity: 90.2%; positive predictive value: 82.3%) than in the high-risk group (< 3 years; sensitivity: 51.8%; specificity: 92.5%; positive predictive value: 90.1%).…”
mentioning
confidence: 85%
“…The hookworm prevalence was 14% (CI [8][9][10][11][12][13][14][15][16][17][18][19][20] in women and 18% (CI 13-23) in children. 19 Mantoux done in Tuberculosis cases showed that 20 (87%) cases had mantoux > 10 mm, and 3 (13%) cases had mantoux 5-10 mm. 3 (13%) children with Tuberculosis were sputum for AFB positive.…”
mentioning
confidence: 99%